2017
DOI: 10.2527/jas2016.0821
|View full text |Cite
|
Sign up to set email alerts
|

Effect of handling intensity at the time of transport for slaughter on physiological response and carcass characteristics in beef cattle fed ractopamine hydrochloride

Abstract: The effects of handling intensity on the physiological response and carcass characteristics of feedlot cattle fed ractopamine hydrochloride were evaluated at the time of transport to slaughter. Eighty steers (BW = 668 ± 36 kg) representing 10 lots of similar breed, frame size, and degree of finish were blocked by lot, stratified by weight, and randomly assigned to 1 of 2 handling intensities (HI) over a 1,600 m dirt alley course: 1) low-stress handling (LSH) or 2) high-stress handling (HSH). For the LSH treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
4
9
0
Order By: Relevance
“…Other studies have explored the change in cattle mobility throughout the marketing process and have reported mobility scores more aligned with what was found in the current study [26][27][28]. Hagenmaier et al [27,28] reported that mobility scores increased (worsened) during the marketing process.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Other studies have explored the change in cattle mobility throughout the marketing process and have reported mobility scores more aligned with what was found in the current study [26][27][28]. Hagenmaier et al [27,28] reported that mobility scores increased (worsened) during the marketing process.…”
Section: Discussionsupporting
confidence: 80%
“…Other studies have explored the change in cattle mobility throughout the marketing process and have reported mobility scores more aligned with what was found in the current study [26][27][28]. Hagenmaier et al [27,28] reported that mobility scores increased (worsened) during the marketing process. For example, Hagenmaier et al [28] found that the prevalence of mobility scores > 1 increased from 7.1% after transport to 20.3% after lairage at the plant and similar changes were reported in Hagenmaier et al [27], with comparable values in the current study as well.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…A substantial amount of research exists on the effects of distance traveled on stress and bruising in cattle, but such research does not include the assessment of cattle mobility or the presence of any abnormalities other than biomarkers of stress, including blood cortisol, lactate, catecholamines, CK, and others ( Mitchell, 1988 ; Jarvis et al, 1995 ; Hoffman et al, 1998 ; Nanni Costa et al, 2003 ). In two separate studies, Frese et al (2016) and Hagenmaier et al (2017) reported that aggressive handling can increase stress markers such as lactate and CK in cattle and can have detrimental effects on mobility. Such associations between blood biomarkers and abnormal mobility are explored further in Lee et al (unpublished data).…”
Section: Discussionmentioning
confidence: 99%